God, guns, gold and glory : American character and its discontents - Langman, Lauren, 1940-; Lundskow, George N., 1964- (Studies in critical social sciences, 2016)
America, beginning as a small group of devout Puritan settlers, ultimately became the richest, most powerful Empire in the history of the world, but having reached that point, is now in a process of implosion and decay. This book, inspired by Frankfurt School Critical Theory, especially Erich Fromm, offers a unique historical, cultural and characterological analysis of American national character and its underlying psychodynamics. Specifically, this analysis looks at the persistence of Puritan religion, as well as the extolling of male toughness and America's unbridled pursuit of wealth. Finally, its self image of divinely blessed exceptionalism has fostered vast costs in lives and wealth. But these qualities of its national character are now fostering both a decline of its power and a transformation of its underlying social character. This suggests that the result will be a changing social character that enables a more democratic, tolerant and inclusive society, one that will enable socialism, genuine, participatory democracy and a humanist framework of meaning. This book is relevant to understanding America's past, present and future.